Pengaruh Work Life Balance (Wlb) dan Lingkungan Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Koperasi Dan UKM (Usaha Kecil Dan Menengah) Kota Sungai Penuh. - M Furqon .; Vicky Brama Kumbara; Dimas Perdana Oskar (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the effect of Work-Life Balance and the work environment on employee performance, with job satisfaction serving as an intervening variable, at the Department of Cooperatives and Small and Medium Enterprises (SMEs) of Sungai Penuh City. This research employed a quantitative method using a survey approach. The population consisted of 46 employees, all of whom were selected as the research sample using the total sampling (census) technique. Data were collected through questionnaires distributed to all respondents. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results of the study indicate that: (1) Work-Life Balance has a positive and significant effect on job satisfaction; (2) the work environment has a positive and significant effect on job satisfaction; (3) Work-Life Balance has a positive and significant effect on employee performance; (4) the work environment has no significant effect on employee performance; (5) job satisfaction has a positive and significant effect on employee performance; (6) job satisfaction mediates the effect of Work-Life Balance on employee performance; and (7) job satisfaction mediates the effect of the work environment on employee performance. These findings indicate that improving Work-Life Balance and creating a conducive work environment can enhance employees' job satisfaction, which in turn contributes to improved employee performance.